3-D Finite element analysis for dynamic response of rigid pavement subjected to moving load - Patil, V.A.; Sawant, V.A.; Deb, Kousik (Journal of Structural Engineering, 2024)
A solution algorithm based on 3D finite element analysis (FEA) is presented to study the dynamic response of concrete pavements subjected to moving loads. The pavement is descritized by using 20 noded isoparametric brick elements. The supporting soil medium is idealized by using elastic continuum model. Kelvin elements are attached to the lowermost boundary elements in order to simulate an infinite soil medium in the vertical direction. The moving vehicle is modeled by a mass supported by a linear spring and dashpot assembly simulating the vehicle suspension system. The vehicle-pavement interaction (VPI) force is modeled with Dirac-delta function. Dynamic equilibrium equation is solved by applying the Newmark-Beta integration scheme. The effects of vehicle-pavement interaction and soil parameters on the dynamic response of pavement are investigated by conducting a parametric study.